Enhanced charge separation ability and visible light photocatalytic performance of graphitic carbon nitride by binary S, B co-doping. (November 2018) - Han, Xiaoxue; Yao, Chengkai; Yuan, Aili; Xi, Fengna; Dong, Xiaoping; Liu, Jiyang
Graphical abstract: Highlights: S, B hertroatoms were successfully doped into g-C3 N4 by thermal treatment. S, B heteroatoms effectively change the intrinsic electronic structure of g-C3 N4 . The SBCN shows much higher photocatalytic activity than CN, SCN and BCN. The SBCN has high photocatalytic stability and reusability. Abstract: As a metal-free visible light photocatalyst, the photocatalytic performance of graphitic carbon nitride (g-C3 N4 ) is limited. To improve the activity of g-C3 N4, we herein report a binary S, B co-doped g-C3 N4 (SBCN) by thermally treating the precursor mixture of thiourea, melamine and boron oxide. Characterization results show the obtained SBCN has ultrathin sheet-like morphology and these doped heteroatoms are uniform distributed in the sample. Compared to the pristine g-C3 N4, the SBCN has a small band gap with additional absorption in visible light region, decreased photoluminescence emission and electric resistance and enhanced photocurrent response. These advantages endue SBCN with excellent photocatalytic activity for degradation of organic dyes, and its reaction rate is 6.5 times higher than that of the g-C3 N4 . Moreover, the successive cycles demonstrate that this SBCN possesses a superior stability and reusability. Finally, we propose a possible photocatalytic mechanism based on the band structure and mainly active species.